Political Preferences of QCA Methods Institutes? A Comment on the Availability and Gender Gap Disparity Problems - Tatarczyk, Dawid (Political Preferences, 2021)
In this research note, I examine a set of two interrelated questions about the Qualitative Comparative Analysis (QCA) methods institutes. First, I assembled and analyzed a novel dataset that tracks every QCA related training worldwide from 2002 to 2018. My examination finds that although QCA trainings are becoming more popular in Europe, the US is still the single most frequent host country for such events. Secondly, I examine the extent to which gender gap exists among QCA instructors. My findings show that female QCA instructors are severely under-represented, which likely limits their academic and professional opportunities. Thus, the QCA research community appears to be marked by the same structural challenges to diversity and gender equality as other areas of political science. Overall, this paper should of interest to scholars interested in the impact of academic infrastructures on future research trajectories as well as those concerned about gender equality in academia.